Potential thresholds of critically increased cardiac-related spinal cord motion in degenerative cervical myelopathy - Pfender, Nikolai; Jutzeler, Catherine R.; Hubli, Michèle; Scheuren, Paulina S.; Pfyffer, Dario; Zipser, Carl M.; Rosner, Jan; Friedl, Susanne; Sutter, Reto; Spirig, José M.; Betz, Michael; Schubert, Martin; et al. (Frontiers in Neurology, 2024)
Introduction New diagnostic techniques are a substantial research focus in degenerative cervical myelopathy (DCM). This cross-sectional study determined the significance of cardiac-related spinal cord motion and the extent of spinal stenosis as indicators of mechanical strain on the cord. Methods Eighty-four DCM patients underwent MRI/clinical assessments and were classified as MRI+ [T2-weighted (T2w) hyperintense lesion in MRI] or MRI− (no T2w-hyperintense lesion). Cord motion (displacement assessed by phase-contrast MRI) and spinal stenosis [adapted spinal canal occupation ratio (aSCOR)] were related to neurological (sensory/motor) and neurophysiological readouts [contact heat evoked potentials (CHEPs)] by receiver operating characteristic (ROC) analysis. Results MRI+ patients (N = 31; 36.9%) were more impaired compared to MRI− patients (N = 53; 63.1%) based on the modified Japanese Orthopedic Association (mJOA) subscores for upper {MRI+ [median (Interquartile range)]: 4 (4–5); MRI−: 5 (5–5); p < 0.01} and lower extremity [MRI+: 6 (6–7); MRI−: 7 (6–7); p = 0.03] motor dysfunction and the monofilament score [MRI+: 21 (18–23); MRI−: 24 (22-24); p < 0.01]. Both patient groups showed similar extent of cord motion and stenosis. Only in the MRI− group displacement identified patients with pathologic assessments [trunk/lower extremity pin prick score (T/LEPP): AUC = 0.67, p = 0.03; CHEPs: AUC = 0.73, p = 0.01]. Cord motion thresholds: T/LEPP: 1.67 mm (sensitivity 84.6%, specificity 52.5%); CHEPs: 1.96 mm (sensitivity 83.3%, specificity 65.6%). The aSCOR failed to show any relation to the clinical assessments. Discussion These findings affirm cord motion measurements as a promising additional biomarker to improve the clinical workup and to enable timely surgical treatment particularly in MRI− DCM patients. Clinical trial registration www.clinicaltrials.gov, NCT 02170155.